2021
DOI: 10.5430/wje.v11n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Instructional Strategies for English Language Learners in Elementary Classrooms

Abstract: In an Eastern U.S. school district, little is understood about how elementary general education teachers apply instructional strategies for English Language Learners (ELLs) in the classroom and which strategies they perceive support academic achievement. The purpose of this basic qualitative study was to explore elementary general education teachers’ reported application of ELL instructional strategies and their perceptions of how those strategies support ELL academic achievement. The study’s conceptual framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
0
0
2
Order By: Relevance
“…Careful pedagogical design is essential when implementing blended learning with EFL learners. Specific strategies are required (Olds et al, 2021) given that the environment is different from a traditional classroom and learners' native language is not English.…”
Section: Discussionmentioning
confidence: 99%
“…Careful pedagogical design is essential when implementing blended learning with EFL learners. Specific strategies are required (Olds et al, 2021) given that the environment is different from a traditional classroom and learners' native language is not English.…”
Section: Discussionmentioning
confidence: 99%
“…Finding result of participants' high degree level of PK is in contrast with Farhan et al (2023) where their research reported participants had a low degree level of PK but both studies have provided insight into the relationship between the pedagogical knowledge of ESL teachers and implementation of classroom learning in the classroom. High mean score obtained by participants regarding their familiarity with teaching strategies is supported by Olds et al (2021), as their article mentioned it is important to comprehend the current methods that general education teachers employ to teach English language to their learners. The finding is also aligns with Akram et al (2021) research which reported enhancing teaching effectiveness and creating a motivating learning environment can be achieved by combining a strong grasp of the subject matter with effective teaching approaches.…”
Section: Pedagogical Knowledge (Pk)mentioning
confidence: 94%
“…Level pendidikan pada usia dini dan sekolah dasar juga tidak luput dari kebutuhan pembelajaran dan pelatihan bahasa Inggris. Siswa tingkat SD lebih cenderung aktif dalam pembelajaran berbasis interaksi sosial dalam kelas (Olds et al, 2021). Kesiapan siswa level SD dalam menghadapi perubahan kurikulum salah satunya pada kesiapan dari sisi psikologis (Angraeni & Yusuf, 2022).…”
Section: Pendahuluanunclassified
“…Rasa percaya diri lain yang didapatkan adalah adanya satu kondisi para peserta merasa telah meningkatkan pengetahuan mereka sehingga akan memberikan dampak merasa lebih terampil dari sebelumnya, namun peserta tetap ditanamkan sikap rendah hati. Level kepercayaan diri siswa SD dalam bidang akademik sama pentingnya dengan prestasi akdemik itu sendiri (Olds et al, 2021). Kepercayaan diri yang terbentuk dapat menjadi dorongan bagi para siswa untuk mengembangkan keberanian mencoba praktek keterampilan lain di masa depan.…”
Section: B Manfaat Kegiatan Abdimasunclassified